2005
DOI: 10.1292/jvms.67.1037
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analysis of Staphylococcus aureus in Skimmed Milk Powder by Real-Time PCR

Abstract: ABSTRACT. A large-scale outbreak of food poisoning caused by consumption of skimmed milk powder contaminated with staphylococcal enterotoxin A (SEA) occurred in Japan. No viable Staphylococcus aureus was detected in the skimmed milk powder, however, sea and nuc genes of S. aureus were detected in it by PCR. The number of S. aureus in skimmed milk powder was estimated by quantitative real-time PCR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 17 publications
0
13
0
2
Order By: Relevance
“…The same may be observed when the milk is not cooled properly after milking. Ikeda et al (2005) reported an outbreak in Japan in 2000, with more than 10 000 cases of staphylococcal enterotoxicosis, milk powder produced from pasteurised milk having been identified as the source of the infection.…”
Section: Resultsmentioning
confidence: 99%
“…The same may be observed when the milk is not cooled properly after milking. Ikeda et al (2005) reported an outbreak in Japan in 2000, with more than 10 000 cases of staphylococcal enterotoxicosis, milk powder produced from pasteurised milk having been identified as the source of the infection.…”
Section: Resultsmentioning
confidence: 99%
“…Several PCR-based methods for foodborne S. aureus identification have been published, targeting only a few different species-specific molecular markers. The predominant target was nuc gene used in either conventional PCR (Ercolini et al 2004;Pinto et al 2005;Ikeda et al 2005;Cremonesi et al 2005) or quantitative real-time PCR (Hein et al 2005;Alarcon et al 2006). Other popular targets were species-specific regions of the DNA coding for 16S or 23S rRNA or coa gene (Cremonesi et al 2005;Baron et al 2004;Sabet et al 2006) and putative transcriptional regulator genes (Liu et al 2005;Goto et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Nakayama et al (2006) konnten sea -sei in künstlich kontaminierter Milch mit Nachweisgrenzen von 10 2 -10 4 KbE/ml nachweisen. Ikeda et al (2005b) untersuchten in Zusammenhang mit einem Ausbruch durch SEA-bildende S. aureus Milchpulver quantitativ auf sea, um damit indirekt auf die Belastung mit S. aureus zu schließen. Eine allgemeine Verwendung quantitativer PCR-Nachweise für SE-Gene zur Abschätzung des Toxingehaltes von Lebensmitteln ist jedoch bei unbekannten Proben kaum möglich, da die Nachweise aufgrund unterschiedlicher Nachweisgrenzen für die einzelnen Toxine für jedes Lebensmittel und jedes Toxin kalibriert werden müßten (Letertre et al, 2003a, Ercolini et al, 2004Nakayama et al, 2006).…”
Section: Polymerasekettenreaktionunclassified
“…Allerdings wurden häufi g nur Reinkulturen oder klinisches Material untersucht. Alarcón et al (2006) und Ikeda et al (2005b) verwendeten den DNeasy Tissue Kit von Qiagen für die Aufbereitung von Rindfl eischproben bzw. Milchpulver.…”
Section: Dna-extraktionunclassified